Effect of tapering diameters with microbottle resonator for formaldehyde (CH2O) liquid sensing - Johari, Md Ashadi Md; Abdul Khudus, Muhammad Imran Mustafa; Jali, Mohd Hafiz; Maslinda, M.S.; Ali, Ummu Umairah Mohamad; Harun, Sulaiman Wadi; Zaidan, A.H.; Apsari, R.; Yasin, M. (Elsevier, 2019)
In this study, we demonstrate the effect of the microbottle resonator (MBR) based on whispering gallery modes (WGMs) with two different diameters of tapered microfibre and its experiment with the formaldehyde (CH2O) liquid sensor. The MBR with the bottle diameter, Db, of 190 μm was categorized by many spectra of transmission modes. Then, the MBR was energized through two tapered microfibres with different diameters, 8 μm and 10 μm. Differences between the two tapered microfibres with the MBR were determined for different concentration levels of sensing liquid. In addition, p-values and stability levels of the two tapered microfibres were calculated. According to the comparison results, the 8 μm tapered microfiber has a much better competency than the 10 μm tapered microfiber when using the MBR. © 2019